On integral solutions of the differential equation of infinite order with polynomial coefficients - Korobeinik, J. F. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ю. Ф. Коробейник. О целых решениях дифференциального уравнения бесконечного порядка J. F. Korobeinik. Begalinės eilės diferencialinės lygties su polinominiais koeficientais sveikieji sprendiniai